A new species of conifer wood Brachyoxylon from the Cretaceous of Eastern China and its paleoclimate significance. (3rd October 2021) - Jiang, Zikun; Wu, Hao; Tian, Ning; Wang, Yongdong; Xie, Aowei
ABSTRACT: A new species of conifer wood, Brachyoxylon zhoui sp. nov., is described from the Lower Cretaceous Guantou Formation of Zhejiang Province, eastern China. The new species is characterised by a mixed type of radial tracheary pitting, araucarioid cross-field pitting, high uniseriate rays, and the occurrence of traumatic resin canals. The new finding represents the second species of Brachyoxylon from the Guantou Formation and it contributes to the further understanding of the forest composition of the Early Cretaceous flora in eastern China.The quantitative analysis of growth ring anatomy indicates that the forest composition was evergreen with a Leaf Retention Time (LRT) of 3–15 years. It is deduced that the Zhejiang Province was dominated by a subtropical to tropical and relatively semiarid climate during the Early Cretaceous.